Estudo do equilíbrio líquido-líquido de sistemas contendo misturas de diesel/biodiesel/etanol/1-butanol - Bonacorso, Rafaela Nunes (2021)
Diesel fuel is a long-chain hydrocarbon mixture and its combustion results in emissions containing particulate matter (PM), hydrocarbons (HC), carbon monoxide (CO), carbon dioxide (CO2) and nitrogen oxides (NOx), which are threats to the environment and can cause severe respiratory problems. The addition of oxygenated fuels such as alcohols and biodiesel to diesel fuel can reduce the emission of pollutants, however, it may cause phase separation between the fuels and can result in serious consequences on the engine operation. The purpose of LLE simulation is to analyze if the components of a mixture form one stable phase or a two-phase solution and to delimitate the unstable area, which suggests the importance of the composition of diesel and its blends to model simulation. UNIFAC is a predictive group contribution model that considers only the interaction between the structural groups present in the solution, which can facilitate LLE and VLE calculations, when in comparison to other models that consider the interaction between each pair of molecules. This study aimed to determine the composition of diesel fuel S10 containing 12% v/v of biodiesel, identify and quantify alcohols in diesel/alcohol fuel blend, and study the LLE of these blends comparing experimental data to thermodynamic simulation. A mixture of 21 n-alkanes plus 4 FAMEs was detected and the higher percentages were found to be between n-undecane (C11) and n-hexadecane (C16). The alcohols eluted with short retention times, reaching the detector before the solvent, and their quantification was in agreement to the samples of known composition, with average precision and recovery of 0.0587% and 99.07% for ethanol and 0.0916% and 95.04% for butanol, respectively. The study also set the UNIFAC-LLE and UNIFAC correlated parameters table accordingly to each structural group, and the LLE calculations considered diesel fuel S10 as a mixture of 10 n- alkanes and 4 FAMEs for thermodynamic modeling simulated on MATLAB®. The model was validated using experimental phase equilibria data of a system containing diesel/biodiesel/ethanol/1-butanol at 278.15 K and 303.15 K. Results have shown that the experimental and calculated data are in a good agreement, with better predictions for UNIFAC correlated. Hence, this method can be utilized to improve the estimation of LLE in diesel blends simulations.